2018
DOI: 10.1002/lary.27426
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Stimulation in Patients With Obstructive Sleep Apnea and an Elevated Body Mass Index: A Multi‐institutional Review

Abstract: 3. Laryngoscope, 128:2425-2428, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
0
27
2
1
Order By: Relevance
“…Not surprisingly, improved outcomes are associated with a lower BMI. This has been shown to be true for other OSA surgical procedures, and UAS implantation does not appear to be an exception, despite some prior evidence to the contrary . Although surgical success has been reported at higher BMIs, the BMI cutoff of 32 by STAR criteria remains a useful guide for surgical decision‐making until there are better preoperative assessment tools available to screen out those patients who would not succeed with UAS therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Not surprisingly, improved outcomes are associated with a lower BMI. This has been shown to be true for other OSA surgical procedures, and UAS implantation does not appear to be an exception, despite some prior evidence to the contrary . Although surgical success has been reported at higher BMIs, the BMI cutoff of 32 by STAR criteria remains a useful guide for surgical decision‐making until there are better preoperative assessment tools available to screen out those patients who would not succeed with UAS therapy.…”
Section: Discussionmentioning
confidence: 96%
“…These patients also had significant improvements with all three demonstrating an AHI ≤10 events/hour after implantation. Similarly, a recent study by Huntley et al showed that patients with a BMI ≥32 kg/m 2 experienced similar rates of surgical success and improvements in AHI and ESS score after HGNS compared to patients with a BMI <32 kg/m 2 . Patients with a mean BMI of 34.37 kg/m 2 ± 2.08 (standard deviation) demonstrated surgical success (<50% reduction in AHI and AHI <20 events/hour) in 92.3% of cases compared to 95.4% of patients with a mean BMI of 27.63 ± 2.48 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…An elevated BMI is known to be a negative predictor for any kind of OSA treatment, [32][33][34] other than a risk factor for OSA development. 2 A retrospective case-control study 35 of 153 patients analyzed the predictive value of a BMI > 32 Kg/m 2 . It demonstrated that HNS is a safe and effective procedure also for higher-BMI group, obtaining comparable clinical outcome in the two cohorts.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%